Purkinje Cardiomyocytes of the Adult Ventricular Conduction System Are Highly Diploid but Not Uniquely Regenerative - Hirofumi Watanabe; Ge Tao; Peiheng Gan; Baylee C. Westbury; Kristie D. Cox; Kelsey Tjen; Ruolan Song; Glenn I. Fishman; Takako Makita; Henry M. Sucov (Journal of Cardiovascular Development and Disease, 2023)
Adult hearts are characterized by inefficient regeneration after injury, thus, the features that support or prevent cardiomyocyte (CM) proliferation are important to clarify. Diploid CMs are a candidate cell type that may have unique proliferative and regenerative competence, but no molecular markers are yet known that selectively identify all or subpopulations of diploid CMs. Here, using the conduction system expression marker Cntn2-GFP and the conduction system lineage marker Etv1CreERT2, we demonstrate that Purkinje CMs that comprise the adult ventricular conduction system are disproportionately diploid (33%, vs. 4% of bulk ventricular CMs). These, however, represent only a small proportion (3%) of the total diploid CM population. Using EdU incorporation during the first postnatal week, we demonstrate that bulk diploid CMs found in the later heart enter and complete the cell cycle during the neonatal period. In contrast, a significant fraction of conduction CMs persist as diploid cells from fetal life and avoid neonatal cell cycle activity. Despite their high degree of diploidy, the Purkinje lineage had no enhanced competence to support regeneration after adult heart infarction.